Gradual cold acclimation induces cardioprotection without affecting β-adrenergic receptor-mediated adenylyl cyclase signaling - Tibenska, V; Benesova, A; Vebr, P; Liptakova, A; Hejnová, L; Elsnicová, B; Drahota, Z; Hornikova, D; Galatík, F; Kolar, D; Vybiral, S; Alánová, P; et al. (Journal of applied physiology (Bethesda, Md., 2020)
Novel strategies are needed that can stimulate endogenous signaling pathways to protect the heart from myocardial infarction. The present study tested the hypothesis that appropriate regimen of cold acclimation (CA) may provide a promising approach for improving myocardial resistance to ischemia/reperfusion (I/R) injury without negative side effects. We evaluated myocardial I/R injury, mitochondrial swelling, and β-adrenergic receptor (β-AR)-adenylyl cyclase-mediated signaling. Male Wistar rats were exposed to CA (8°C, 8 h/day for a week, followed by 4 wk at 8°C for 24 h/day), while the recovery group (CAR) was kept at 24°C for an additional 2 wk. The myocardial infarction induced by coronary occlusion for 20 min followed by 3-h reperfusion was reduced from 56% in controls to 30% and 23% after CA and CAR, respectively. In line, the rate of mitochondrial swelling at 200 μM Ca2+ was decreased in both groups. Acute administration of metoprolol decreased infarction in control group and did not affect the CA-elicited cardiprotection. Accordingly, neither β1-AR-Gsα-adenylyl cyclase signaling, stimulated with specific ligands, nor p-PKA/PKA ratios were affected after CA or CAR. Importantly, Western blot and immunofluorescence analyses revealed β2- and β3-AR protein enrichment in membranes in both experimental groups. We conclude that gradual cold acclimation results in a persisting increase of myocardial resistance to I/R injury without hypertension and hypertrophy. The cardioprotective phenotype is associated with unaltered adenylyl cyclase signaling and increased mitochondrial resistance to Ca2+-overload. The potential role of upregulated β2/β3-AR pathways remains to be elucidated.NEW & NOTEWORTHY We present a new model of mild gradual cold acclimation increasing tolerance to myocardial ischemia/reperfusion injury without hypertension and hypertrophy. Cardioprotective phenotype is accompanied by unaltered adenylyl cyclase signaling and increased mitochondrial resistance to Ca2+-overload. The potential role of upregulated β2/β3-adrenoreceptor activation is considered. These findings may stimulate the development of novel preventive and therapeutic strategies against myocardial ischemia/reperfusion injury.
Keywords: Receptors, Adrenergic, beta; mitochondria; adenylyl cyclase; beta-adrenergní receptory; Male; Rats, Wistar; adrenergní látky; mužské pohlaví; potkani Wistar; Acclimatization; krysa rodu Rattus; Adrenergic Agents; β-adrenergic receptors; adenylátcyklasy; Animals; cold acclimation; zvířata; Rats; cardioprotection; Adenylyl Cyclases; aklimatizace